2018
DOI: 10.1155/2018/6170502
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Landmark- and Outline-Based Geometric Morphometrics for Discriminating Mosquito Vectors in Ratchaburi Province, Thailand

Abstract: It is often challenging to identify mosquito vectors in the field based on morphological features due to their similar morphologies and difficulties in obtaining undamaged samples but is required for their successful control. Geometric morphometrics (GM) overcomes this issue by analyzing a suite of traits simultaneously and has the added advantages of being easy to use, low cost, and quick. Therefore, this research compared the efficiency and precision of landmark- and outline-based GM techniques for separatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…whitmorei with the IOL2 analysis. This research was consistent with previous studies conducted in terms of species identification of Aedes, Culex, and Anopheles mosquitoes in Thailand, which found that OTL was a potential technique (Chaiphongpachara 2018). Comparison of the efficiency of each outline for species separation via cross-validated classification scores established that EOL had the highest potential, especially for Cx.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…whitmorei with the IOL2 analysis. This research was consistent with previous studies conducted in terms of species identification of Aedes, Culex, and Anopheles mosquitoes in Thailand, which found that OTL was a potential technique (Chaiphongpachara 2018). Comparison of the efficiency of each outline for species separation via cross-validated classification scores established that EOL had the highest potential, especially for Cx.…”
Section: Discussionsupporting
confidence: 90%
“…The difference of shape between mosquitos species in each cell may emanates from the specificity between species of mosquitoes with internal and external cells of wings. Previous research has compared two GM methods, including landmark-based and outline-based GM approaches for identification of mosquito vectors in Ratchaburi Province, Thailand, and the results of size analysis revealed that both methods are different (Chaiphongpachara 2018). This clearly indicates that even though it is the same wing, the different positions of the analysis can affect the results of the size between species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometric morphometric (GM) techniques are a modern approach recognized as useful for the identification of species in many insects (Dujardin 2011;Chaiphongpachara 2018). Currently, many types of insects that have obstacles in identification by a morphological method in class Insecta has been confirmed such that the GM approach can help solve this problem, such as three members of the mosquito species of the Maculatus group (Anopheles maculatus, An.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of GM is that it is a cheap method which does not require much equipment, is easy to use and is rapid (Rohlf 2002). Currently, both GM methods have been applied to the study of entomology, including mosquito (Chaiphongpachara 2018;, beetle (Lamb et al 2013), blow-fly (Sontigun et al 2017), spider (Fernández and Marugán 2017), pupae of flies (Chaiphongpachara and Laojun 2019), and bee (De Souza et al 2015). Although it is an effective alternative tool, not all organisms can be identified by this technique, so it is necessary to study the feasibility of applying it to each organism (Ruangsittichai et al 2011).…”
Section: Introductionmentioning
confidence: 99%